MAKALAH SEMINAR HASIL PENELITIAN NILAI HUMANISTIK DALAM SERAT ABIMANYU KRAMA - Purba Asmoro; Titin Masturoh; Kuwato (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
ABSTRACT -nilai Kearifan Lokal Melalui Transliterasi dan Terjemahan Naskah Pewayangan sebagai Model Penyusunan Lakon uses the aesthetic approach and theory of puppetry. Javanese social cultural approach is used to analyze moral valves by analyzing the humanistic valves contained in Serat Abimanyu Krama. The result shows that Serat Abimanyu Krama contains the essential valves reflected in the character's behaviour. Some of them behave agree with in the society. The essencial valves in Serat Abimanyu Krama incude the valves of: sacrificing, courage, patience and obedient, fair and wise, and customs of wedding, bridal accompanist, bridal departing, and custom of panggih (bridal rendezvom). On the contrary, some of the characters behave aside from the social customs, for example, (1) Prabu Kalasiya: who succeed in kidnapping Siti Sendari and hicle her in his couentry; (2) Lesmana Mandra Kumara who is not successful in his desire to marry Siti Sendari for it is based on a bad thing.